MODEL KURIKULUM INKLUSIF DALAM MEMBANGUN LINGKUNGAN BELAJAR RAMAH ANAK - Muzayinah, Siti; Nurfuadi, Nurfuadi (STAI Sangatta Kutai Timur, 2025)
Inclusive education is a global concern aimed at ensuring equal educational access for all children, including those with special needs. In Indonesia, the implementation still faces obstacles, especially related to access, public stigma, and limited support facilities. This study explores the inclusive curriculum model in creating a child-friendly learning environment. Using a descriptive qualitative approach, the research involves literature review and observation of real phenomena regarding inclusive education. Data were analyzed through content analysis to formulate an inclusive school curriculum. The findings reveal that curriculum planning must be based on individual assessments, supported by collaborative teaching involving special education teachers. Inclusive learning is implemented through curriculum modifications, individual learning programs, and appropriate evaluations. The research highlights the importance of teacher competence, parental support, and adequate facilities. In conclusion, the inclusive curriculum model can support the realization of child-friendly schools, promote equality in education, and empower children with special needs to reach their potential.